Circadian Rhythm Gene PER3 Negatively Regulates Stemness of Prostate Cancer Stem Cells via WNT/β-Catenin Signaling in Tumor Microenvironment - Li, Qilin; Xia, Ding; Wang, Zhihua; Liu, Bo; Zhang, Jing; Peng, Ping; Tang, Qiujun; Dong, Jie; Guo, Juan; Kuang, Dong; Chen, Weimin; Mao, Jing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer (PCa) cells are heterogeneous, containing a variety of cancer cells with phenotypical and functional discrepancies in the tumor microenvironment, where prostate cancer stem cells (PCSCs) play a vital role in PCa development. Our earlier studies have shown that ALDHhiCD44+ (DP) PCa cells and the corresponding ALDHloCD44– (DN) PCa cells manifest as PCSCs and non-PCSCs, respectively, but the underlying mechanisms regulating stemness of the PCSCs are not completely understood. To tackle this issue, we have performed RNA-Sequencing and bioinformatic analysis in DP (versus DN) cells in this study. We discovered that, PER3 (period circadian regulator 3), a circadian rhythm gene, is significantly downregulated in DP cells. Overexpression of PER3 in DP cells significantly suppressed their sphere- and colony-forming abilities as well as tumorigenicity in immunodeficient hosts. In contrast, knockdown of PER3 in DN cells dramatically promoted their colony-forming and tumor-initiating capacities. Clinically, PER3 is downregulated in human prostate cancer specimens and PER3 expression levels are highly correlated with the prognosis of the PCa patient. Mechanistically, we observed that low levels of PER3 stimulates the expression of BMAL1, leading to the phosphorylation of β-catenin and the activation of the WNT/β-catenin pathway. Together, our results indicate that PER3 negatively regulates stemness of PCSCs via WNT/β-catenin signaling in the tumor microenvironment, providing a novel strategy to treat PCa patients.